Leveraged property cycles - Ivan Jaccard (European Central Bank (ECB), 2021)
This paper studies the effects of imperfect risk-sharing between lenders and borrowers on commercial property prices and leverage. The key friction is that agents use different discount rates to evaluate future flows. Eliminating this pecuniary externality generates large reductions in the volatility of real estate prices and credit. Therefore, policies that enhance risk-sharing between lenders and borrowers reduce the magnitude of boom-bust cycles in real estate prices. We also introduce health shocks to study the effect of the COVID-19 crisis on the commercial property market.
Keywords: E32; E44; G10; E23; 330; Leverage Cycle; Pecuniary Externalities; Asset Pricing; Incomplete Markets